ACESSO À JUSTIÇA E DESJUDICIALIZAÇÃO: A (in)efetividade da realização da mediação, conciliação e arbitragem nas serventias notariais e registrais - MATHEUS CERAZI SARTORI (2024)
The present work aims to conceptualize and address access to justice and its perspective as a human right and its evolution as a fundamental right aimed at citizenship, based on legislative implementation to carry out conciliation, mediation and arbitration in note and record services and their difficulties. Knowing the deficient issues of access to justice in Brazil, conciliation, mediation and arbitration in a notary's office were debated as they are useful instruments to assist with existing problems with judicialization. The research also sought to analyze whether the regulations implemented to carry out conciliation and mediation in registry offices are having an effect; if they were, it would demonstrate their effectiveness in guaranteeing access to justice; If not, it would present the reasons and solutions for the problems presented, including the arbitration that was carried out by comparison as it was a recent legislative implementation. Given the results found, it is concluded that the achievement is being negligible, even more so when compared to private chambers. With this, it instrumentalized possible public policy implementations aimed at improving the problems presented. The research methodology was based on the hypothetical-deductive method through an applied and explanatory research approach, with bibliographical research on the “Scielo” and “Google Scholar” platforms and in classic works on the topics, as well as a thematic analysis the most recent data from the “justice in numbers” reports from the National Council of Justice (CNJ), “notary in numbers”, carried out by the Association of Notaries and Registrars of Brazil and “arbitration in numbers”. Furthermore, a bibliographical research was carried out to collect printed and digital sources of whether or not conciliation and mediation hearings were held in the registry offices of the State of São Paulo and of the aforementioned sessions in private chambers